Fracture behaviour of fibre-reinforced composite materials subjected to shear loading: an experimental and numerical study - Liu, Haibao; Zhou, Jin; Kong, Xiangshao; Li, Shipeng (Elsevier, 2022)
Compared to fibre-dominated behaviour, a response dominated by the matrix under shear loading can considerably limit the load-bearing capability and restrict the utilisation of composite materials. It is therefore practically significative to understand the shear response of composite materials. This paper presents a detailed experimental and numerical investigation on the fracture behaviour of composite laminates subjected to shear-dominated loading. Composite specimen with a lay-up of [(0/90)4/0]S are tested using the V-Notched Rail (VRS) shear test method. Subsequently, the Scanning Electron Microscope (SEM) investigation is also conducted on the fracture surfaces of the tested specimens to get insights into the damage mechanisms due to shear loading. In addition, a high-fidelity computational damage model is developed to predict the shear fracture behaviour of fibre-reinforced composites. Simulation results, including loading response, strain distribution and shear fracture, well correlated with experimental results, which demonstrates the predictive capability of the developed elastic-plastic damage model.
Keywords: Polymer-matrix composites; Shear fracture; Damage mechanisms; finite element analysis; Computational mechanics